“Analisa Dissenting Opinion Dalam Hasil Putusan Permohonan Perkara Nomor 35/PUU/XXII/2024 Terhadap Pasal 35 Ayat 1 UU No 13 Tahun 2023 Tentang Ketenagakerjaan - Ohandi, Max Andrew; Syam, Radian (Postulat, 2025)
This research highlights Judge Guntur Hamzah's dissenting opinion in the Constitutional Court's decision regarding Article 35 paragraph (1) of Law no. 13 of 2023 concerning Employment. He criticized the phrase "recruit the required workforce clarity" which has the potential to give rise to legal uncertainty and discrimination, especially regarding age limits and appearance requirements. This dissenting opinion provides an alternative perspective that encourages critical reflection on the majority decision. The implication is the need for legal revisions for justice and inclusiveness, punctuation increasing public awareness about discrimination. The research method uses normative juridical methods with a literature approach. Research recommendations include reviewing Article 35 paragraph (1), stricter law enforcement, and developing fair employment policies.